2013
DOI: 10.1242/dev.099390
|View full text |Cite
|
Sign up to set email alerts
|

Evf2 (Dlx6as) lncRNA regulates ultraconserved enhancer methylation and the differential transcriptional control of adjacent genes

Abstract: SUMMARYSeveral lines of evidence suggest that long non-coding RNA (lncRNA)-dependent mechanisms regulate transcription and CpG DNA methylation. Whereas CpG island methylation has been studied in detail, the significance of enhancer DNA methylation and its relationship with lncRNAs is relatively unexplored. Previous experiments proposed that the ultraconserved lncRNA Evf2 represses transcription through Dlx6 antisense (Dlx6as) transcription and methyl-CpG binding protein (MECP2) recruitment to the Dlx5/6 ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 31 publications
5
114
0
Order By: Relevance
“…Berghoff and his colleagues 27) found that lncRNA-Evf2 could repress Dlx5/6 gene expression by regulating Dlx5/6 enhancer site-specific methylation. Martens et al 28) found that lncRNA-SRG1 transcript across the SER3 promoter interferes with the binding of activators, thus regulating SER3 repression.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Berghoff and his colleagues 27) found that lncRNA-Evf2 could repress Dlx5/6 gene expression by regulating Dlx5/6 enhancer site-specific methylation. Martens et al 28) found that lncRNA-SRG1 transcript across the SER3 promoter interferes with the binding of activators, thus regulating SER3 repression.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Studies on Evf2, the first lncRNA member of larger classes of ucRNAs/t-UCRs, show that Evf2 (Dlx6os1, Dlx6as) is transcribed on the opposite strand, antisense to Dlx6, and therefore also belongs to the class of OS/NATs (Feng et al, 2006). Although antisense transcription predicted that Evf2 would have cis-regulatory effects, multiple experiments suggest that Evf2 exhibits both trans and cis effects (Feng et al, 2006;Bond et al, 2009;Berghoff et al, 2013). Chromatin immunoprecipitation (ChIP) experiments show that Evf2 increases the binding of transcriptional activators (DLX1/2; Zerucha et al, 2000) and the repressor methyl-CpG binding protein 2 (MECP2; Nan et al, 1997) to key Dlx5/6 enhancers (Zerucha et al, 2000) with a repressive outcome (Bond et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, it was shown that transcription through the Evf2 locus controls the levels of Dlx6 in cis; after disengaging the polymerase, Evf2 then acts in trans to modulate methylation of the Dlx5/6 enhancer and transcription of Dlx5. Therefore, by regulating the cellular levels of the Dlx5 and Dlx6 TFs, Efv2 controls GABAergic interneuron activity (Berghoff et al, 2013;Bond et al, 2009). …”
Section: Lncrnas Required For Neuronal Developmentmentioning
confidence: 99%